Combinatorial Principle in the Use of Drum (Kendhang) Formulae in Gamelan Music of Yogyakarta. From Prescriptive Models to the Interpretation of a Composition: the Case of Kendhang Pinatut. - Luca Pietrosanti (IJCAS (International Journal of Creative and Arts Studies), 2014)
In this paper, I address the question to the use of drums (kendhang) in the traditional Gamelan music of Yogyakarta, by presenting some prescriptive models (or formulas). I illustrate how, the use of different prescriptive models in a composition follow what I labeled as “Combinatorial Principle”. In order to describe the essential elements of this principle, I will analyze the modalities of interaction between a very flexible drum formula (known as pinatut) and three other prescriptive models for drum within some exemplary pieces of traditional Gamelan music. The concept of combinatorial principle illustrated in these pages, on the one hand explains the way of interaction between the drum’s rhythmic formulas and their capacity to influence the choices made by the entire orchestra during a performance; on the other hand, through this principle we are able to trace a path that attempts to understand the “deep structures” that are the basics of making music in Gamelan tout court. Through the perspective of the combinatorial principle it is possible to analyze the prescriptive models and techniques of many other instruments of the Gamelan of central Java.